2018
DOI: 10.1016/j.scitotenv.2017.12.179
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the contribution of riparian soils to the provision of ecosystem services

Abstract: Riparian areas, the interface between land and freshwater ecosystems, are considered to play a pivotal role in the supply of regulating, provisioning, cultural and supporting services. Most previous studies, however, have tended to focus on intensive agricultural systems and only on a single ecosystem function. Here, we present the first study which attempts to assess a wide range of ecological processes involved in the provision of the ecosystem service of water quality regulation across a diverse range of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 126 publications
0
23
0
2
Order By: Relevance
“…The lower Yellow River is a perched river with a main-channel width of 0.5 to 3.0 km and a riparian zone with width of 5 to 20 km that was restricted by the left and right levees [36,37]. As such, the riparian zone is larger than that used in the studies conducted by Hazlett et al [47] (5 m and 75 m from the lakeshore), Schilling et al [48] (1, 20, and 40 m from river), Cierjacks et al [49] (518±50 m from main channel), Smith et al [23] (transects 36 m long and separated by 6 m), Lidman et al [12] (4, 12 and 22 m from river), and de Sosa et al [45] (2 and 50 m from river). These differences in distance used, which could be determined by river size and order, topographic feature, and land use and land cover [52], can lead to differences in hydrologic dynamics, geomorphic dynamics, and ecological processes.…”
Section: Response Of Soil Nutrients To Lateral Distance Of Riparian Zonementioning
confidence: 76%
See 4 more Smart Citations
“…The lower Yellow River is a perched river with a main-channel width of 0.5 to 3.0 km and a riparian zone with width of 5 to 20 km that was restricted by the left and right levees [36,37]. As such, the riparian zone is larger than that used in the studies conducted by Hazlett et al [47] (5 m and 75 m from the lakeshore), Schilling et al [48] (1, 20, and 40 m from river), Cierjacks et al [49] (518±50 m from main channel), Smith et al [23] (transects 36 m long and separated by 6 m), Lidman et al [12] (4, 12 and 22 m from river), and de Sosa et al [45] (2 and 50 m from river). These differences in distance used, which could be determined by river size and order, topographic feature, and land use and land cover [52], can lead to differences in hydrologic dynamics, geomorphic dynamics, and ecological processes.…”
Section: Response Of Soil Nutrients To Lateral Distance Of Riparian Zonementioning
confidence: 76%
“…For instance, Burger et al [44] and Smith et al [23] indicated that riparian soils close to the river have higher levels of organic C and N when compared with remnant riparian zones that were far distances from the river. However, several studies observed little or no effect of distance from the river on riparian soil physicochemical properties [45,[46][47][48], even though significant differences were observed among different riparian habitats. The authors attributed their findings to the habitat characteristics that they selected.…”
Section: Response Of Soil Nutrients To Lateral Distance Of Riparian Zonementioning
confidence: 99%
See 3 more Smart Citations